From DNA to sustainability: the genomics approach in livestock production - Juan Carlos Gutiérrez-Añez (Revista Científica)
The livestock industry has used genetic selection to improve phenotypic characteristics for decades. The  identification of characteristics in the population, such as adaptation, disease resistance, production capacity, and specific phenotypic characteristics, combined with the use of directed and assisted reproduction techniques, have been the tools that have allowed us to reach current production levels in the livestock industry. Since the discovery of DNA and the advancement of molecular genetics, it is well known that phenotypic characteristics (milk production, meat production, and absence of horn, among many others) are conditioned and governed mainly by DNA. Thus, indirectly, genetic improvement programs based on the measurement of the characters of interest, selection, and control of reproduction to multiply the selected-desired character have as their principle the intervention and control of the DNA replicated in the next generations. On the other hand, genomic sequencing is the technology that has advanced the fastest in the last decade. Its applications and benefits for human development and improving the quality of life of current and future generations are innumerable and have tremendous implications. For instance, genomic selection has been proposed as a valuable tool to combat climate change. In this sense, genomic selection uses information from many genetic markers or single nucleotide polymorphisms (SNPs) in conjunction with measurements (phenotypes) of essential traits in livestock to improve selection accuracy, reduce the generation intervals, and increase genetic gains since the observation can be read and estimated with a DNA sequencing before the population express the character even before the animal is born. Therefore, genomic selection has generated significant buzz as it has the potential to revolutionize livestock production globally, allowing farmers to be more productive using fewer resources (feed, water) to fill the rapidly changing climates and human needs.